An Internally Validated Nomogram for Predicting the Likelihood of Improvement of Clinical Global Impression in Patients with Lifelong Premature Ejaculation Treated with Dapoxetine. Issue 12 (13th November 2020) - Hou, Guangdong; Gao, Ming; Zhang, Lei; Dun, Xinlong; Zheng, Yu; Wang, Fuli; Yan, Fei; Zheng, Wanxiang; Yin, Chuanmin; Yuan, Jiarui; Zhang, Geng; Meng, Ping; et al.
Abstract: Background: Although the introduction of dapoxetine has ushered in a new era in the treatment of premature ejaculation, many patients with lifelong premature ejaculation (LPE) exhibit an unimproved clinical global impression even after treatment with dapoxetine. Aim: To investigate independent predictors of the improvement of Clinical Global Impression (iCGI) in patients with LPE treated with dapoxetine and develop a nomogram to predict a patient's likelihood of achieving iCGI. Methods: Data of 243 patients with LPE diagnosed at Xijing Hospital (Xi'an, China) and Northwest Women's and Children's Hospital (Xi'an, China) from January 2019 to May 2020 were analyzed. Independent predictors of iCGI were identified, and a nomogram was developed using R software based on a multivariate logistic regression model. The predictive accuracy of the nomogram was measured using the area under the receiver operating characteristic curve. The nomogram was calibrated by comparing predictions with observations. Main Outcome Measures: The primary outcome was the patient-rated Clinical Global Impression of Change scale score after a 4-week course of dapoxetine treatment, which was collected via an online questionnaire. A Clinical Global Impression of Change score of ≥1 was defined as iCGI in this study. Results: Patients with LPE with at least a bachelor's degree, a self-reported intravaginal ejaculation latency time of >1 minute, and an International Index of Erectile Function question 5 score of ≥3 were independent factors associated with achieving iCGI, whereas a Premature Ejaculation Diagnostic Tool question 1 score of ≥2 was an independent factor negatively associated with achieving iCGI. The predictive accuracy of the nomogram, which was developed by integrating all variables with independent predictive significance, was 0.710 (95% confidence interval: 0.702–0.718). In addition, the calibration plot demonstrated excellent agreement between predictions and observations. Clinical Implications: If the predictive performance of our nomogram is further proven in multiple external validations, it can be used to select suitable patients for dapoxetine treatment, thereby reducing the number of patients discontinuing treatment. Strengths & Limitations: This study developed the first nomogram for predicting the likelihood of achieving iCGI in patients with LPE treated with dapoxetine. However, our nomogram was not externally validated using independent cohorts from other institutions. Conclusion: This study identified several independent predictors of iCGI in patients with LPE treated with dapoxetine. An effective nomogram was developed to predict their likelihood of achieving iCGI. External validations using data of Western patients with LPE are required to test the broader applicability of this Chinese patient-based tool.